Faster‐acting insulin aspart: earlier onset of appearance and greater early pharmacokinetic and pharmacodynamic effects than insulin aspart. Issue 7 (8th May 2015) - Heise, T.; Hövelmann, U.; Brøndsted, L.; Adrian, C. L.; Nosek, L.; Haahr, H.
<x xml:space="preserve">Abstract</x> Aims To evaluate the pharmacokinetics and pharmacodynamics of faster‐acting insulin aspart and insulin aspart in a randomized, single‐centre, double‐blind study. Methods Fifty‐two patients with type 1 diabetes (mean age 40.3 years) received faster‐acting insulin aspart, insulin aspart, or another faster aspart formulation (not selected for further development), each as a single 0.2 U/kg subcutaneous dose, under glucose‐clamp conditions, in a three‐way crossover design (3–12 days washout between dosing). Results Faster‐acting insulin aspart had a faster onset of exposure compared with insulin aspart, shown by a 57% earlier onset of appearance [4.9 vs 11.2 min; ratio 0.43, 95% confidence interval (CI) 0.36; 0.51], a 35% earlier time to reach 50% maximum concentration (20.7 vs 31.6 min; ratio 0.65, 95% CI 0.59; 0.72) and a greater early exposure within 90 min after dosing. The greatest difference occurred during the first 15 min, when area under the serum insulin aspart curve was 4.5‐fold greater with faster‐acting insulin aspart than with insulin aspart. Both treatments had a similar time to maximum concentration, total exposure and maximum concentration. Faster‐acting insulin aspart had a significantly greater glucose‐lowering effect within 90 min after dosing [largest difference: area under the curve for the glucose infusion rate (AUCGIR), 0–30 min ratio 1.48, 95% CI 1.13; 2.02] and 17% earlier time to reach 50% maximum glucose infusion rate (38.3 vs 46.1 min; ratio 0.83, 95% CI 0.73; 0.94). The primary endpoint (AUCGIR, 0–2 h) was 10% greater for faster‐acting insulin aspart, but did not reach statistical significance (ratio 1.10, 95% CI 1.00; 1.22). Both treatments had similar total and maximum glucose‐lowering effects, indicating similar overall potency. Conclusions Faster‐acting insulin aspart was found to have earlier onset and higher early exposure than insulin aspart, and a greater early glucose‐lowering effect, with similar potency.